2017
DOI: 10.1111/phpp.12281
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of photodynamic therapy for the treatment of actinic cheilitis

Abstract: Photodynamic therapy, as carried out in this trial, was not an efficacious therapeutic option for treating patients with actinic cheilitis included in this sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 41 publications
0
27
1
2
Order By: Relevance
“…Since some studies found that PDT is not an efficacious treatment for AC (94,95), some authors aimed at finding new methods to improve this technique. Fontes et al evaluated the efficacy of MAL-PDT with previous application of CO 2 laser in eight patients with AC of the lower lip.…”
Section: Updates In Pdt In the Treatment Of Other Precancerous Skin Lmentioning
confidence: 99%
“…Since some studies found that PDT is not an efficacious treatment for AC (94,95), some authors aimed at finding new methods to improve this technique. Fontes et al evaluated the efficacy of MAL-PDT with previous application of CO 2 laser in eight patients with AC of the lower lip.…”
Section: Updates In Pdt In the Treatment Of Other Precancerous Skin Lmentioning
confidence: 99%
“…Since then, several publications have demonstrated the efficacy of this modality for the treatment of AC . A recent publication demonstrated limited efficacy in 16 patients treated with conventional PDT, however, the patients only underwent two PDT sessions . Based on our data, we suggest that many patients require more than two sessions to achieve remission, thus there is a need to simplify the procedure and reduce costs.…”
Section: Discussionmentioning
confidence: 68%
“…Ten studies were included in this review and processed for data extraction (Table ). Thirty‐eight full texts were excluded for the following reasons: case report or fewer than 10 cases (Chakrabarty, Mraz, Geisse, & Anderson, ; Ghasri, Admani, Petelin, & Zachary, ; McDonald, Laverick, Fleming, & White, ; Rossi, Assad, Buggiani, & Lotti, ); follow‐up of <6 months or not specified (Alexiades‐Armenakas & Geronemus, ; Armenores, James, Walker, & Huilgol, ; Berking et al, ; Calzavara‐Pinton, Rossi, Sala, & Italian Group For Photodynamic Therapy, ; Chaves et al, ; de Godoy Peres, Aigotti Haberbeck Brandão, Rodarte Carvalho, Dória Filho, & Plapler, ; Kim, Song, & Kim, ; Menta Simonsen Nico, Rivitti, & Lourenço, ; Menta Ulrich et al, ; Ribeiro et al, ; Spyridonos, Gaitanis, Tzaphlidou, & Bassukas, ; Ulrich et al, ); abstract, comment, or literature review (Alexiades−Armenakas, ; Dinani, Topham, Derrick, & Atkinson, ; Goldman, ; Kuwahara & Rasberry, ; Larios, Alevizos, & Rigopoulos, ; Laws, Wilde, & Grabski, ); insufficient data regarding treatment, lesion location, or outcome (Jorizzo, Weiss, & Vamvakias, ; Nelson et al., 2007; Ntomouchtsis et al, ; Rossoe, Tebcherani, Sittart, & Pires, ; Sand, Altmeyer, & Bechara, ; Sotiriou, Apalla, Koussidou, & Ioannides, ; Stough, Bucko, Vamvakias, Rafal, & Davis, ); studies including patients with a previous diagnosis of SCC or those with SCC in the sample (Dufresne, Cruz, Zeikus, Perlis, & Jellinek, ; Laws et al, ; Smith, Germain, Yeager, & Skelton, ; Zaiac & Clement, ); and articles that were not in English (Ceylan, Erboz, Özdemir, & Kazandi, ; Ceylan, Özdemir, & Kazandi, ; Ulrich et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, an estimated 95% of SCC of the lip originates from AC (Gomes et al., ). Consequently, an early diagnosis and treatment of AC are of the utmost importance (Chaves, Torezan, Lourenço, & Neto, ; Choi, Kim, & Song, ).…”
Section: Introductionmentioning
confidence: 99%